2006
DOI: 10.1177/070674370605101209
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and Triiodothyronine Augmentation of Antidepressants

Abstract: There may be no advantage to a combination of these augmenting agents, although we failed to show separation between active treatments and placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…There are several open-label trials supporting the efficacy of T 3 augmentation of SSRI for TRD, as reviewed by Cooper-Kazaz and Lerer [64]. However, a single RCT did not show differences between T 3 , lithium and T 3 plus lithium as augmenting agents for TRD [65]. As discussed previously, the STAR*D trial compared T 3 with lithium augmentation for TRD and found no significant differences in remission rates, although T 3 was better tolerated [60].…”
Section: Resultsmentioning
confidence: 99%
“…There are several open-label trials supporting the efficacy of T 3 augmentation of SSRI for TRD, as reviewed by Cooper-Kazaz and Lerer [64]. However, a single RCT did not show differences between T 3 , lithium and T 3 plus lithium as augmenting agents for TRD [65]. As discussed previously, the STAR*D trial compared T 3 with lithium augmentation for TRD and found no significant differences in remission rates, although T 3 was better tolerated [60].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were identified that included a randomization component (Appelhof et al, 2004;CooperKazaz et al, 2007;Joffe et al, 2006;Nierenberg et al, 2006;Posternak et al, 2007). These are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These are summarized in Table 1. Three were enhancement studies in which T3 and a SSRI were administered concurrently from the inception of treatment (Appelhof et al, 2004;CooperKazaz et al, 2007;Posternak et al, 2007) and two were augmentation studies in which T3 was added to the ongoing treatment of patients who had not responded (Joffe et al, 2006;Nierenberg et al, 2006). No open enhancement studies were identified and no specifically designed acceleration studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also mixed non-resistant with varying percentages (8–38%) of TRD patients. There are several open-label studies showing benefits for thyroid augmentation in TRD patients using SSRIs as a primary treatment,4648 and one controlled study showing no difference between augmentation with T3, lithium, and T3 plus lithium in TRD patients 49. The STAR*D study compared T3 and lithium augmentation and found no significant difference in remission rates between the two, but did find T3 was better tolerated 50…”
Section: Pharmacotherapy For Trdmentioning
confidence: 99%